The (Possible) Future of Cyborg Healthcare: Depictions of Disability in Cyberpunk 2077. (2nd October 2021) - Fox, Alice
ABSTRACT: In the social imagination, cyborgs often invoke visions of super-humans entangled with cutting-edge technology capable of surpassing the limits of the human body. However, the focus on futuristic high-tech hybrids often overlooks the challenges and demands of disabled people – people who already experience life as cyborgs. Differently abled people are frequently under-or-un-represented within popular culture and media. And representation is often limited to super-abled tropes or redemption through technology. Video games are not exceptional in their representation of disabled people. This review will focus more intensely on how disability is depicted in the American dark future of Cyberpunk 2077. Ultimately recognizing that while this game could benefit from rendering its themes of interdependency, trust, maintenance, more salient for a general audience, Cyberpunk 2077 ultimately embraces a more robust representation of healthcare challenges and experiences of differently abled people than many other games featuring cyborgs.